Origins and processes of groundwater salinization in the urban coastal aquifers of Recife (Pernambuco, Brazil): A multi-isotope approach - Cary, Lise; Petelet-Giraud, Emmanuelle; Bertrand, Guillaume; Kloppmann, Wolfram; Aquilina, Luc; Martins, Veridiana; Hirata, Ricardo; Montenegro, Suzana; Pauwels, Hélène; Chatton, Eliot; Franzen, Melissa; Aurouet, Axel; et al. (The Science of the total environment, 2015)
In the coastal multilayer aquifer system of a highly urbanized southern city (Recife, Brazil), where groundwaters are affected by salinization, a multi-isotope approach (Sr, B, O, H) was used to investigate the sources and processes of salinization. The high diversity of the geological bodies, built since the Atlantic opening during the Cretaceous, highly constrains the heterogeneity of the groundwater chemistry, e.g. Sr isotope ratios, and needs to be integrated to explain the salinization processes and groundwater pathways. A paleoseawater intrusion, most probably the 120kyB.P. Pleistocene marine transgression, and cationic exchange are clearly evidenced in the most salinized parts of the Cabo and Beberibe aquifers. All 87Sr/86Sr values are above the past and present-day seawater signatures, meaning that the Sr isotopic signature is altered due to additional Sr inputs from dilution with different freshwaters, and water–rock interactions. Only the Cabo aquifer presents a well-delimitated area of Na-HCO3 water typical of a freshening process. The two deep aquifers also display a broad range of B concentrations and B isotope ratios with values among the highest known to date (63–68.5‰). This suggests multiple sources and processes affecting B behavior, among which mixing with saline water, B sorption on clays and mixing with wastewater. The highly fractionated B isotopic values were explained by infiltration of relatively salty water with B interacting with clays, pointing out the major role played by (palaeo)-channels for the deep Beberibe aquifer recharge. Based on an increase of salinity at the end of the dry season, a present-day seawater intrusion is identified in the surficial Boa Viagem aquifer. Our conceptual model presents a comprehensive understanding of the major groundwater salinization pathways and processes, and should be of benefit for other southern Atlantic coastal aquifers to better address groundwater management issues. •A multi-isotope approach was used to assess the salinization sources and processes.•The geological unit diversity constrains the groundwater chemistry heterogeneity.•A global Pleistocene seawater intrusion and related cationic exchange are evidenced.•The δ11B in groundwater presents highly fractionated values (63–68.5‰).•A present-day seawater intrusion is identified locally in the surficial aquifer.